A sequential injection system for spectrophotometric determination of ketoconazole - Safwan M. Fraihat (Maejo International Journal of Science and Technology, 2014)
Sequential injection analysis (SIA) with spectrophotometric detection is used for a fast determination of ketoconazole in pure and pharmaceutical preparations. The developed method is based on oxidation of ketoconazole with cerium ion in an acidic medium, which leads to the formation of a coloured product that absorbs at a wavelength of 496 nm. Then automation of the method is developed using the SIA technique. All variables that affect the reaction response are studied and optimised using univariate and simplex optimisation. The method is applicable for the determination of ketoconazole in the range of 20-120 µg mL-1.